Análise e melhoria da gestão da manutenção no maquinário agrícola de uma empresa do setor sucroenergético - Pimentel, Anne Caroline Fagundes (2017)
The consumer market is currently characterized by the high-quality demand, provided by globalization and technological development, creating a scenario of great competitiveness among organizations. The maintenance activities, in this context, is a competitive factor in which operational excellence moved on from being a market differential, to become a basic requirement. In this way, the present study aims to analyze the maintenance management system of the baling agricultural machinery in a company of the sugarcane sector and to propose improvements based on the concepts of the maintenance management.